Dataset for Developing the evidence base for surface-flow treatment wetlands targeting phosphorus removal and carbon sequestration - Souleymane, Ayisha Affo; Dotro, Gabriela; Lyu, Tao; Grabowski, Robert C. (Cranfield University, 2026)
Constructed wetlands are increasingly recognised as low-energy nature-based solutions for wastewater treatment, particularly for small and rural communities facing tightening nutrient discharge regulations. This thesis investigated the performance and long-term resilience of four full-scale surface flow treatment wetlands in the United Kingdom and Ireland using datasets spanning up to 14 years. The research combined water quality assessment, phosphorus fractionation, sediment and biomass analysis, hydraulic tracer testing, greenhouse gas estimation, and Weibull survival-based reliability modelling at the Clifton, Ingoldisthorpe, Langham, and Glaslough Integrated Constructed Wetlands (ICWs). Overall, the thesis demonstrated that integrating reliability analysis, hydraulic function, and internal storage dynamics provides a more process-based understanding of long-term wetland sustainability.
These datasets were generated as part of a PhD research programme investigating the performance, phosphorus dynamics, hydraulic behaviour, and reliability of full-scale surface flow treatment wetlands operating under secondary and tertiary wastewater treatment conditions in the United Kingdom and Ireland. Data were collected from the Clifton, Glaslough, Ingoldisthorpe, and Langham Integrated Constructed Wetlands (ICWs) between 2010 and 2025. The repository contains cleaned datasets exported from the original project workbooks and includes water quality monitoring data, flow records, phosphorus fractionation results, sediment and biomass analyses, dissolved gas measurements, tracer study outputs, and derived performance calculations. Data were generated through routine field monitoring, laboratory analysis, and hydraulic tracer testing using standard analytical methods. Parameters include, where applicable, ammonium, orthophosphate, total phosphorus, total nitrogen, suspended solids, BOD, COD, dissolved oxygen, pH, redox potential, metals, and hydraulic variables. Users should note that some datasets contain operationally derived variables and site-specific abbreviations. These datasets are intended to support transparency, reproducibility, and future research into nature-based solutions and long-term wetland performance under tightening environmental regulations.
Keywords: Hydraulic behaviour; wastewater treatment; redox dynamics; sediment phosphorus fractionation; oxygen limitation; treatment reliability; greenhouse gas emissions; P–k–C model*; ammonium; compliance; treatment wetlands; constructed wetlands